Analisis perbandingan tingkat akurasi model Financial Distress pada perusahaan sektor transportasi dan Logistik - Hardiansyah Yuris Wirawan; Dewi Pangestuti (Politeknik Ganesha Medan, 2022)
Data on the average profit and loss and the movement of sectoral growth in transportation and logistics sector companies which experienced a decline indicate that investor confidence in these sectors is decreasing. The purpose of this study was to determine whether there were differences in the prediction results of the financial distress model and to find out how much accuracy each prediction model tested and which model had the highest level of accuracy. The sample in this study was selected by purposive sampling technique and obtained a total of 22 companies that became the research sample. The research method uses a non-parametric test, namely the Kruskal-Wallis test and the level of accuracy test. The results of this study conclude that based on statistical tests there are significant differences in the use of financial distress prediction models. In addition, the accuracy test states that the model with the highest level of accuracy is produced by the Taffler model with an accuracy of 76.14%, followed by the Grover model with an accuracy of 69.32% and finally the Fulmer model with an accuracy of 63.64%.